Properties of sourdough starters for breadmaking - Lau, Siew Wen
Sourdough fermentation consumes only water and flour to initiate spontaneous biochemical reactions of wild lactic acid bacteria (LAB) and yeast for leavening, acidification and shelf life extension of bakery products, especially bread. The quality of sourdough is usually determined by physicochemical properties, rheological properties, sensory characteristics and microbial properties. Since sourdough is still not well known in local market and most researches reported on sourdoughs are not climatised to weather in our region, this research was conducted with aims to measure and predict physicochemical properties as well as identify beneficial bacteria of sourdough starters. Sourdough starters were made using wheat, sorghum and rye flours for comparison. 50 grams of flour and 50 grams of distilled water were mixed for each flour type for a l0-day-long fermentation at room temperature of 30.5 + 2.5"C. Each of them was refreshed daily by discarding 50 grams for the first refresh and 100 g for subsequent refresh thereaft.er adding flour and water of 50 grams each after taking samples for analyses. Daily analyses were conducted for measuring'sourdough starter's leavening height, pH, total trtratable acidity (TTA) and concentration of fermentable sugars. A microbial test was conducted at the end of fermentation. The analysed properties of sourdough starters are interconnected and interdependent. Through the fermentation period, pH of sourdough starters decreased while TTA increased. Wheat sourdough starter achieved the lowest pH (3.23) and highest TTA (14.8 ml) at the end of fermentation, followed by sorghum and rye. Sorghum sourdough starter consisted of the least concentration of sugars, which ranged between 0 and 0.936 g/100g sample for all sugars types and exhibited almost similar trend of sugar concentration changes as wheat and rye sourdough samples due to three-phase microbial succession. As the greatest height increment among all samples, aleavening height of 82.9IYo was shown by wheat sourdough starter on day 2 of fermentation. Statistical models were fitted for sourdough starter properties estimation during the fermentation period. Wheat sourdough starter had the lowest microbial diversity, with only one significant class of Bacilli (90.2Yo) while the rest was mostly unclassified. L. brevis, L. paraplantarum, L. helveticus, Enterococcus andStreptococcus are some important bacteria detected in sourdough starters. Based on the properties studied, the sourdough starters developed in this research had the potential for bread volume increment in breadmaking process as well as shelf life extension in breads. The consumption of sourdough bread aids in enhancing body health too.